Etika Bermedsos dalam Perspektif Hadits - Alfi Salwa Qibty (Gunung Djati Conference Series, 2023)
This research aims to discuss hadith about the ethics of social media from a hadith perspective. This study uses a qualitative approach by interpreting hadith texts, applying descriptive analytical methods through the takhrij hadith method and correlating its consumption through morals. Regarding the formal object in it, that is related to the study of hadith, while for the material object, namely the hadith about the ethics of social media from a hadith perspective. As for the context in this research, it is relevant to morals and social interaction through current technology. The results and discussion of this study indicate that the quality of hadith narrated by Muslim No.06 has the status of authentic, which fulfills the qualifications of maqbul hadith for Islamic practice. This study concludes that the public needs to address this by always being patient in responding to anything related to social media, whether in the form of information or news or in the form of other things. It also teaches about the values of aqidah and morals in their relevance to faith and good behavior in Islam.